A MANFAAT SENAM LANSIA UNTUK MENGATASI HIPERTENSI DI PUSKESMAS TANAH TINGGI - nanda, febri yus (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
Health development according to the 2009 law on health aims to increase awareness, willingness and ability to live healthily for each individual in order to realize the highest degree of health for the community, as a form of developing socially and economically productive human resources. One of the goals of achieving health development is that each individual is obliged to live a healthy life. At this time there has been a change in one's healthy life or lifestyle, which has an impact on the 2020 shift in disease patterns where the burden of disease is no longer dominated by communicable diseases, but also non-communicable diseases such as hypertension (RI Ministry of Health, 2016). Hypertension or blood pressure disease High blood pressure is a disturbance in the blood vessels resulting in the supply of oxygen and nutrients. This condition causes blood pressure in the arteries to increase and the heart has to work harder to meet this demand. The number of people with hypertension every year around the world continues to increase. Exercises that can be done by the elderly to reduce blood pressure are by doing the SKJ exercise for the elderly. The SKJ exercise for the elderly is carried out with movements that involve most of the body's muscles, according to daily movements and contain movements against body weight by giving weight between the right halves. and left equally. This community service activity has benefits for both students and patients. After doing elderly exercise there is a difference in blood pressure before and after being given the elderly exercise treatment in systolic and diastolic hypertension.